Monitoring the agri-food system in Myanmar: Mechanization service providers - January 2023 survey round - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
A phone survey was conducted in January 2023 to understand the effects of COVID‑19 and political instability on Myanmar’s mechanization service providers (MSPs). MSPs are crucial to enabling smallholder farmers to undertake a range of power-intensive farm and post-harvest operations in a timely manner. This note reports on the results of this survey, the tenth in a series of phone surveys, and trends from earlier surveys.